Unexpected increase in indoor pollutants after the introduction of a smoke‐free policy in a correctional center. (10th August 2015) - He, C.; Knibbs, L. D.; Tran, Q.; Wang, H.; Laiman, R.; Wang, B.; Gu, Y.; Morawska, L.
Abstract: Correctional centers (prisons) are one of the few non‐residential indoor environments where smoking is still permitted. However, few studies have investigated indoor air quality (IAQ) in these locations. We quantified the level of inmate and staff exposure to secondhand smoke, including particle number (PN) count, and we assessed the impact of the smoking ban on IAQ. We performed measurements of indoor and outdoor PM2.5 and PN concentrations, personal PN exposure levels, volatile organic compounds (VOCs), and nicotine both before and after a complete indoor smoking ban in an Australian maximum security prison. Results show that the indoor 24‐h average PM2.5 concentrations ranged from 6 (±1)  μ g/m 3 to 17 (±3)  μ g/m 3 pre‐ban. The post‐ban levels ranged from 7 (±2)  μ g/m 3 to 71 (±43)  μ g/m 3 . While PM2.5 concentrations decreased in one unit post‐ban, they increased in the other two units. Similar post‐ban increases were also observed in levels of PN and VOCs. We describe an unexpected increase of indoor pollutants following a total indoor smoking ban in a prison that was reflected across multiple pollutants that are markers of smoking. We hypothesise that clandestine post‐ban smoking among inmates may have been the predominant cause.